Ultimate bearing capacity of strip footing on sands under inclined loading based on improved radial movement optimization. Issue 2 (1st February 2021) - Jin, Liangxing; Zhang, Hanchao; Feng, Qixuan
Abstract : Improved radial movement optimization (IRMO) is adopted to investigate the critical slip surface and ultimate bearing capacity of a rough embedded strip footing on sands under inclined loading using the upper-bound limit analysis. Based on the Mohr–Coulomb yield criterion, a planar kinematically admissible multi-block failure mechanism of strip footing under inclined loading is formulated. The soil is assumed to be elastic–perfectly plastic material with an associated flow rule, and a solution procedure for the ultimate bearing capacity is established based on the virtual work principle. The results show that IRMO can calculate the ultimate bearing capacities efficiently, accurately and stably. The size and shape of normalized failure envelopes and inclination factors depend on the friction angle and embedment ratio. Moreover, the errors of the joint and individual influences of soil unit weight and surcharge for the bearing capacity of strip footing decrease with increasing load inclination angle α .